Evaluasi Perubahan Warna Semen Ionomer Kaca dengan Penambahan Ekstrak Etanol Propolis Trigona spp. - Deviyanti Pratiwi; Advita Azalia; Achmad E. Z. Hasan; Florencia L. Kurniawan; Dewi L. Margaretta (Universitas Sam Ratulangi, 2023)
Glass ionomer cement (GIC) is constantly modified to improve its properties and expand its use in dental practice. One of the modifications studied is the addition of ethanolic extract of propolis (EEP), a natural resin material with various pharmacological effects. Modifications made with EEP were found to increase the antibacterial effect of GIC, but this modified material also impacted the physical properties of the cement. This study aimed to evaluate the color change of GIC caused by the addition of EEP. This was a laboratory experimental study. The GIC color was assessed using the VITA Easyshade V spectrophotometer. A total of 20 cylindrical GIC samples measuring 10 mm (diameter) x 2 mm (height) were divided into four groups based on the proportion of EEP added to the GIC liquid, as follows: A, conventional GIC (control); B, GIC modified with EEP at 25% w/w; C, GIC modified with EEP at 30% w/w; and D, GIC modified with EEP at 35% w/w. The color assessment was performed after the samples were immersed in artificial saliva and incubated for 24 hours. The post hoc test between the three experimental groups and the control group showed a significant difference (p<0.05). The ΔE value between the three experimental groups and the control group showed a value greater than 3.3. In conclusion, the addition of EEP in the proportions of 25%, 30%, and 35% resulted in significant color change of GIC. Keywords: glass ionomer cement; ethanolic extract of propolis; Trigona spp.; discoloration Abstrak: Semen ionomer kaca (SIK) terus dimodifikasi untuk meningkatkan sifat dan memperluas penggunaannya dalam praktik kedokteran gigi; salah satunya ialah penambahan ekstrak etanol propolis (EEP), suatu bahan resin alami yang memiliki berbagai efek farmakologis. Modifikasi dengan EEP dapat meningkatkan efek antibakteri dari SIK, namun bahan modifikasi ini juga berdampak terhadap sifat fisik semen. Penelitian ini bertujuan untuk mengevaluasi perubahan warna SIK yang disebabkan oleh penambahan EEP Trigona spp. Jenis penelitian ialah eksperimental laboratorik. Warna diukur menggunakan spektrofotometer VITA Easyshade V. Sebanyak 20 sampel SIK silinder berukuran 10 mm (diameter) x 2 mm (tinggi) dibagi dalam empat kelompok uji berdasarkan proporsi EEP yang ditambahkan ke cairan SIK: A, SIK konvensional (kontrol); B, SIK modifikasi EEP 25% w/w; C, SIK modifikasi EEP 30% w/w; dan D, SIK modifikasi EEP 35% w/w. Pengukuran warna dilakukan setelah sampel direndam dalam saliva buatan dan diinkubasi selama 24 jam. Uji post hoc antara ketiga kelompok perlakuan dengan kelompok kontrol menunjukkan perbedaan bermakna (p<0,05). Nilai ΔE antara ketiga kelompok perlakuan dengan kelompok kontrol menunjukkan nilai yang lebih besar dibandingkan 3,3. Simpulan penelitian ini ialah penambahan EEP dalam proporsi 25%, 30%, dan 35% secara bermakna mengakibatkan perubahan warna SIK. Kata kunci: semen ionomer kaca; ekstrak etanol propolis; Trigona spp.; perubahan warna